Eksplorasi Etnomatematika Terhadap Pola Gambar Bidang Permainan Tradisional Engklek Pada Anak - Nasiruddin, Fathimah Az.zahra; Ramadhan, Nur Rezky; alviani, vivi (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
Culture is actually the habit or way of life of a group of people in a community that continues for generations, while mathematics is a science of logical assessment of the form, order, magnitude, and concepts related to each other. Ethnomatematika is a link or uniting between culture and mathematics learning, where a cultural result can be a source of mathematics learning in schools. With engklek games that are still very popular among children in East Aralle Village, this can be one of the sources of learning mathematics, especially in the pattern of drawing this field of play. This field research conducted by interview, observation, and documentation method aims to describe the results of ethnomatematic exploration on the drawing pattern of the field of play engklek. The results showed that in the drawing pattern of the field of play engklek in East Aralle Village contains mathematical elements, including the concept of flat build and nets - cube nets